Corrigendum to “The existence of kuda lumping performances in terms of character education based on the principles of Pancasila” - Dionisius Heckie Puspoko Jati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
In the original published version of this article, the authors inadvertently omitted the Acknowledgement section. We sincerely apologize for this oversight and any confusion it may have caused. The updated PDF versions of the article reflect the necessary corrections, including the addition of the Acknowledgement section. Acknowledgments The authors would like to express their sincere gratitude to the Directorate of Research and Community Service (DRPM) of Universitas Kristen Satya Wacana (UKSW) for the support and research funding that enabled the successful completion of this study. This research was conducted under Decree Number 086/SPK-JAD/RIK/07/2025, entitled “The Existence of Kuda Lumping Performing Arts Viewed from Character Education in the Principles of Pancasila.” The authors also extend their appreciation to all parties who contributed academically and technically to the implementation of this research. The authors apologize for any inconvenience these issues may have caused to readers and thank the editorial team for facilitating these corrections.